The Effects of Plyometric Training Combined with Weighted Sandbags and Elastic Resistance Bands on Leg Muscle Power and Blocking Skills in Volleyball - Rachote, Ratchanok; Kumpuang, Chankit; Chimwong, Luxamee (Research Community and Social Development Journal, 2024)
Background and Objective: Exercise training is important in helping to develop muscle strength and physical fitness in athletes. Especially in the sport of volleyball that requires high power and agility. Therefore, this research aims to evaluate and compare the results of plyometric training combined with the use of weighted sandbags and the use of resistance bands with elastic bands on leg muscle power and blocking skills in volleyball. Methology: Conduct research according to quantitative research methods. with Quasi-experimental design, two experimental groups were assigned, each group containing 15 people, totaling 30 people. There was no random sampling because the groups had already been arranged. The research tools consisted of two training programs and a test with concordance index values of 0.99, 0.98, and 0.96, respectively, which were used to collect data by testing before and after the 4th, 6th, and 8th weeks. For data analysis, statistics were used to find the average. Standard deviation and test the hypotheses using a one-way repeated-measures analysis of variance and two-way repeated-measures variance. Results: 1) The experimental group had increased muscle power and blocking skills before training with a higher increase in blocking skill than leg muscle power. 2) Different training sessions had different effects on leg muscle power and blocking skill every week. Meanwhile, the duration of training affects leg muscle power and blocking skills. There is an interaction between the duration of training and the joint training program. Statistically significant at the 0.05 level, but different training programs had no effect on leg muscle power and blocking skills. Discussion: The results of the study indicated that the effectiveness of both plyometric training programs was able to increase blocking skills higher than leg muscle power in volleyball. This shows the importance of selecting training methods that are appropriate and specific to the training objectives. Suggestion: Further research should be conducted on the effects of implementing a training program with a larger sample and at different ages of volleyball players.